On the Use of Infrared Thermography for the Estimation of Melting Enthalpy - Clément Mailhé (Applied Sciences, 2021)
A calorimetry method based on infrared thermography is showing promise for material screening, allowing the simultaneous detection of phase transitions of multiple samples at a time, hence enabling the establishment of phase diagrams in a record time. The working principle of this method is similar to the one of Differential Thermal Analysis. Therefore, this work aims at identifying if the melting enthalpy of materials could be estimated on the same basis using infrared thermography. In this work, the melting of six eutectic mixtures of fatty acids is estimated under three considerations. The results are compared to Differential Scanning Calorimetry measurements and literature data. The accuracy of the method is discussed and improvements are proposed.